Gelatin structure and composition linked to hard capsule dissolution: A review. (January 2015) - Duconseille, Anne; Astruc, Thierry; Quintana, Naira; Meersman, Filip; Sante-Lhoutellier, Véronique
Abstract: Gelatin obtained from pig skin constitutes about 50% of world production and is mainly composed of collagen extracted from skin by acidic baths and thermal treatments. The gelatin is used to make various products, notably hard gelatin capsules (HGC) which of varying solubility in water. This issue has been known for many years and has been, and remains, a subject of study and debate. The main reason for low gelatin dissolution rates is its tendency to form cross-links in the denatured collagen chains under specific conditions which stabilize the gel network and prevent dissolution. As it is extracted from animal tissues, gelatin may contain molecules other than collagen (sugars, lipids and other proteins) which may react with collagen chains to form covalent bonds. Although this biopolymer has been the subject of numerous publications, its structure and composition is not well defined. Indeed, there are many differences from an article to another. Consequently, the causes of HGC dissolution are not well identified and controlled. Graphical abstract: Highlights: Gelatin cross-links reduce hard gelatin capsules dissolution in water. Hydrophobic, hydrogen and electrostatic bonds contribute to aggregates in gelatin. High molecular weights and aggregates in gelatin reduce its dissolution.